2017
DOI: 10.18869/acadpub.jpcp.5.1.27
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Islamic Lifestyle and Addiction Potential Among Adolescents

Abstract: Objective: This study was conducted to investigate the association between Islamic lifestyle and addiction potential among adolescents residing in Eslamshahr City, Iran.Methods: This was a cross sectional study. The statistical population consisted of all students attending public high schools during 2012-2013 academic year in Eslamshahr City. The sample size was 211, who were selected through multi-stage cluster sampling method. The Islamic lifestyle and addiction potential questionnaires were used to collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Chan et al, in another study, indicated that spirituality led to an increase in individuals' psychological well-being [25]. Also, people with an Islamic lifestyle are less susceptible to substance abuse [26].…”
Section: Introductionmentioning
confidence: 99%
“…Chan et al, in another study, indicated that spirituality led to an increase in individuals' psychological well-being [25]. Also, people with an Islamic lifestyle are less susceptible to substance abuse [26].…”
Section: Introductionmentioning
confidence: 99%